Preterm birth, unplanned hospital contact, and mortality in infants born to teenage mothers in five countries: An administrative data cohort study. Issue 6 (28th April 2020) - Harron, Katie; Verfuerden, Maximiliane; Ibiebele, Ibinabo; Liu, Can; Kopp, Alex; Guttmann, Astrid; Ford, Jane; van der Meulen, Jan; Hjern, Anders; Gilbert, Ruth
Abstract: Background: Young maternal age is associated with lower birthweight and higher rates of preterm birth and childhood hospitalisations. Internationally, teen pregnancy rates vary widely, reflecting differences in social, welfare, and health care factors in different cultural contexts. Objectives: To determine whether the increased risk of adverse infant outcomes among teenage mothers varies by country, reflecting different national teenage birth rates and country‐specific social/welfare policies, in Scotland (higher teenage pregnancy rates), England, New South Wales (NSW; Australia), Ontario (Canada), and Sweden (lower rates). Methods: We used administrative hospital data capturing 3 002 749 singleton births surviving to postnatal discharge between 2010 and 2014 (2008‐2012 for Sweden). We compared preterm birth (24‐36 weeks' gestation), mortality within 12 months of postnatal discharge, unplanned hospital admissions, and emergency department visits within 12 months of postnatal discharge, for infants born to mothers aged 15‐19, 20‐24, 25‐29, and 30‐34 years. Results: Compared to births to women aged 30‐34 years, risks of adverse outcomes among teenage mothers were higher in all countries, but the magnitude of effects was not related to country‐specific rates of teenage births. Teenage mothers had between 1.2% (95% confidence interval [CI] 0.7, 1.7, Sweden) and 2.0% (95% CI 1.4, 2.5, NSW) more preterm births, and between 9.8 (95% CI 7.2, 12.4, England) and 19.7 (95% CI 8.7, 30.6, Scotland) more deaths per 10 000 infants, compared with mothers aged 30‐34. Between 6.4% (95% CI 5.5, 7.4, NSW) and 25.4% (95% CI 24.7, 26.1, Ontario), more infants born to teenage mothers had unplanned hospital contacts compared with those born to mothers aged 30‐34. Conclusions: Regardless of country, infants born to teenage mothers had universally worse outcomes than those born to older mothers. This excess risk did not vary by national rates of livebirths to teenage mothers. Current mechanisms to support teenage mothers have not eliminated maternal age‐related disparities in infant outcomes; further strategies to mitigate excess risk in all countries are needed.